A CORPUS BASED STUDY OF VERB COLLOCATIONS IN SENIOR HIGH SCHOOL TEXTBOOKS BY INDONESIAN GOVERNMENT - HERI SAMUDRA (S2 PBI Universitas Ahmad Dahlan, 2022)
This research aims to 1) find out the most 20 types of lexical verbs frequencies in senior high school textbooks, 2) to determine the verb + noun collocation that the most frequently I senior high school textbooks, and 3) to compare the use underuse and overuse of the lexical verb + noun collocations in the senior high school textbooks with Corpus of Contemporary American English (COCA) and British National Corpus (BNC) Descriptive quantitative as the approach that is used by the research to analyze the frequencies of the most 20 types of lexical verbs in senior high school textbooks. Data sources are from the 20 verb collocations that are in three series textbooks of senior high sch